VD_FINDINFO HC / 2010 / 123 vom 15. Februar 2010 - VD Tribunal cantonal (2010)
JUGEMENT DE DIVORCE, PERSONNE DIVORCÉE, OBLIGATION D'ENTRETIEN, ENFANT DU CONJOINT | 134 al. 2 CC, 138 al. 1 CC, 145 al. 1 CC, 279 al. 1 CC, 286 al. 2 CC